EKSISTENSI DAN NILAI BUDAYA PERMAINAN ”MAIN LADANG” PADA MASYARAKAT DESA OLAK, KABUPATEN BATANGHARI - Adelsa Gusmiva; Ayu Masyitah; Winda Agil Zuhriana; Diana Pangestuti; Femi Br Ginting; Dhea Amanda; Annisa Humaila; Arum Desta Widyawati; Khusnul Qotimah; Ifta Juita Ananda; Cahya Karina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the cultural values and social meanings contained in the traditional game ”Main Ladang” in Olak Village, Muara Bulian Subdistrict, Batanghari Regency. Traditional games are part of local cultural heritage that contribute to children’s social interaction and character development. However, the rapid development of digital technology has changed children’s play patterns, resulting in a decline in the practice of traditional games. This research employed a descriptive qualitative approach. Data were collected through interviews with community members who have knowledge and experience related to the traditional game ”Main Ladang”. The data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings show that “Main Ladang” is a local variant of the Gobak Sodor game which reflects cultural values such as togetherness, cooperation, unity, and sportsmanship. The game is played in open spaces using simple line patterns that reflect the agrarian lifestyle of the community. Although the game still exists, its intensity has decreased due to the increasing use of digital technology among children. Therefore, ”Main Ladang” has the potential to be used as an educational medium for character development in elementary school children as well as a means of preserving local cultural heritage.